The short term continuous darkness affects brain and behavior in a sex‐dependent manner: A comparative study in C57BL/6 male and female mice. (31st December 2021) - Singh, Dhyanendra
Abstract: Background: Standard light‐dark cycle (12h light and 12h dark) has an imperative role in keeping experimental animals healthy and adaptive. If it gets perturbed, it can negatively impact the brain, behavior, and Physiology. The circadian clock (central clock) of hypothalamic suprachiasmatic nuclei received light signals from the environment. Subsequently, in collaboration with the peripheral clocks of the tissues, the central clock transformed these light signals into oscillations in behavior and physiology to maintain homeostasis in coping with environmental fluctuations or stressors. To understand how light‐dark cycle disruption affects the brain and, as a result, behavior, it's critical to simultaneously look at the molecular and behavioral changes. Further, sex is one of the inevitable variables neglected in neurobiology and behavioral study even after the advancement of science in the 20 th century Method: In the current study, we evaluated the influence of the altered light‐dark cycle on the brain (prefrontal cortex), stress response, and behavior of C57BL/6 male and female mice by exposing them to the continuous darkness (0h light and 24h dark) for three weeks Result: Our results show that constant darkness leads to the change in behavior (in the open field test), the prefrontal cortex (pro‐ and anti‐inflammatory genes and neurotrophic factors), and stress response (stress hormones) in a sex‐dependent manner Conclusion: The present study laid the foundation for understanding how the altered light‐dark cycle perturbed behavior, brain, and stress response in a sex‐dependent way.